The tobacco sector in the Republic of Macedonia - Tuna, Emelj (2008)
The tobacco sector is an important part of the Macedonian agriculture and the economy in general. This project is giving an overall prospective of the Macedonian tobacco industry, and it points out its comparative advantages and disadvantages. The core question at the beginning was "Whether Macedonian tobacco industry is competitive or not?" In order to determine the answer to this question, both descriptive and empirical approaches are used. The essential part of this study was the approach developed by Porter or the determinants of national advantage. The description of this sector was developed following the concept of Porter's Diamond model with an overall aim of determining this sector's strengths, weaknesses, threats and opportunities in a so called SWOT analysis. This study also includes some competitiveness index calculations.